Efficient computation of locally monotonic regression - Restrepo Palacios, Alfredo; de la Vega, Ramiro (Revista de Ingeniería, 1997)
So far, the applicability of locally monotonic regression has been limited by the high computational costs of the available algorithms that compute them. We present a powerful theoretical result about the nature of these regressions. As an application, we give an algorithm for the computation of lomo-3 regressions which reduces the complexity of the task, from exponential to polynomial.